2021
DOI: 10.1002/jcla.24061
|View full text |Cite
|
Sign up to set email alerts
|

Association between apolipoprotein E gene polymorphism and nonalcoholic fatty liver disease in Southern China: A case‐control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…While early observational studies investigating the relation of the APOE polymorphism and the risk of fatty liver disease, or NAFLD in particular, hardly find any significance [ 35 - 37 ], Sazci et al reported an apparent accumulation of APOE epsilon 3 homozygotes in NASH patients in 2008 [ 38 ]. This finding was then corroborated in case-control studies [ 39 , 40 ] identifying APOE epsilon 4 as the protective allele. Since then, several genome- and exome-wide association analyses have been confirming an association of the APOE4/APOE3-distinguishing SNP (rs429358) with liver function, liver fat content and fatty liver disease on different ethnic backgrounds [ 41 - 45 ].…”
Section: Introductionsupporting
confidence: 53%
“…While early observational studies investigating the relation of the APOE polymorphism and the risk of fatty liver disease, or NAFLD in particular, hardly find any significance [ 35 - 37 ], Sazci et al reported an apparent accumulation of APOE epsilon 3 homozygotes in NASH patients in 2008 [ 38 ]. This finding was then corroborated in case-control studies [ 39 , 40 ] identifying APOE epsilon 4 as the protective allele. Since then, several genome- and exome-wide association analyses have been confirming an association of the APOE4/APOE3-distinguishing SNP (rs429358) with liver function, liver fat content and fatty liver disease on different ethnic backgrounds [ 41 - 45 ].…”
Section: Introductionsupporting
confidence: 53%
“…Groups of continuous data analysis were performed with Mann-Whitney U -test. The allele (ε2, ε3, ε4) and genotype (E2/E2, E2/E3, E2/E4, E3/E3, E3/ E4, E4/E4) are respectively of the control group (without CVD or tumor) as a reference [ 51 53 ]. Chi-square test was performed for comparing allele frequencies composition ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia affects the distribution of tight-junction (TJ) proteins and nutrient transporters across the BBB, altering its permeability and function as shown in in vitro models [ 75 ] and magnetic resonance imaging (MRI) in patients with T2DM [ 76 ]. The CNS effects of insulin resistance and diabetes were shown to be more marked in individuals with the apolipoprotein E alleles ε4 and ApoE-ε4 allele, which was found to be present in 16.6% of patients with NALFD [ 77 ].…”
Section: Molecular Evidencementioning
confidence: 99%